2018
DOI: 10.1007/s00360-018-1176-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific activation of calpain system in hindlimb unloading rats and hibernating Daurian ground squirrels: a comparison between artificial and natural disuse

Abstract: To determine whether the regulation of calpain system is involved in non-hibernators and hibernators in disused condition, the soleus (SOL) and extensor digitorum longus (EDL) muscles were used for investigating the muscle mass, the ratio of muscle wet weight/body weight (MWW/BW), fiber-type distribution, fiber cross-sectional area (CSA), and the protein expression of MuRF1, calpain-1, calpain-2, calpastatin, desmin, troponin T, and troponin C in hindlimb unloading rats and hibernating Daurian ground squirrels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
4
14
0
Order By: Relevance
“…While PWB led to a transient body weight loss in male rats (Mortreux et al, 2018(Mortreux et al, , 2019a,c), we did not observe any significant fluctuations of the females' body weight, either compared to the control group or to their pre-suspension baseline. This sex-based difference has been reported previously after exposure to 14 and 30 days of hindlimb unloading (Il'ina-Kakueva, 2002;David et al, 2006;Chang et al, 2018;Deschenes et al, 2018), and in our study, was further associated with a similar food intake, which was eventually greater at the end of the experiment in the PWB40 group when normalized to animals' body weight, compared to the PWB100 controls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While PWB led to a transient body weight loss in male rats (Mortreux et al, 2018(Mortreux et al, , 2019a,c), we did not observe any significant fluctuations of the females' body weight, either compared to the control group or to their pre-suspension baseline. This sex-based difference has been reported previously after exposure to 14 and 30 days of hindlimb unloading (Il'ina-Kakueva, 2002;David et al, 2006;Chang et al, 2018;Deschenes et al, 2018), and in our study, was further associated with a similar food intake, which was eventually greater at the end of the experiment in the PWB40 group when normalized to animals' body weight, compared to the PWB100 controls.…”
Section: Discussionsupporting
confidence: 90%
“…In our pilot study, females exposed to 14 days of PWB40 did not exhibit a decreased soleus mass; however, we were able to detect a significant atrophy of the type I myofibers, which was not associated with a myofiber type switch throughout the muscle (Figure 3D). The absence of fiber-type switch has previously been described in female rats (Il'ina-Kakueva, 2002;Deschenes et al, 2018), though others have not identified this (Chang et al, 2018). Taken together, our analysis of the soleus muscle allows us to hypothesize that in females, preferential myofiber atrophy occurs prior to myofiber-type switch and gross muscle atrophy, however, it remains to be confirmed in longer experiments.…”
Section: Discussionsupporting
confidence: 70%
“…The muscle fiber cross-sectional area (CSA) and fiber type composition were measured by 191 immunofluorescent analysis as described by our laboratory previously (Chang et al 2018b). Briefly, 192 5 mm of the mid-belly of lateral gastrocnemius muscle was cut into 10-μm thick frozen muscle 193 cross-sections at -20℃ with a cryostat (Leica, Wetzlar, CM1850, Germany).…”
Section: Immunofluorescent Analysis 190mentioning
confidence: 99%
“…Daurian ground squirrels during hibernation, whereas the expression of calpastatin, an endogenous 121 inhibitor of calpains, is increased in both (Chang et al 2018b). Calpain can degrade substrates such 122 as desmin, troponin T, troponin I, titin, alpha-fodrin and alpha-actinin, (Barta et al 2005).…”
mentioning
confidence: 99%
“…Molecular mechanisms lying at the core of muscle mass retention in hibernators have been broadly discussed recently 23,[28][29][30][31][32][33][34][35][36][37][38] . Various mechanisms are suggested to be responsible both for the decrease of atrophy development during torpor and for the activation of protein synthesis and muscle mass retention during arousals.…”
mentioning
confidence: 99%